Angiofibroma Localized in the Sphenoid Sinus - Alper Yenigun; Fadlullah Aksoy; Omer Vural; Orhan Ozturan (Case Reports in Otolaryngology)
Juvenile nasopharyngeal angiofibroma is the most common benign tumor of the nasopharynx with complaints of unilateral nasal obstruction and recurrent nosebleeds in the young male population. Despite being a benign tumor, it can be aggressively destructive in surrounding tissues and bones by acting locally. The gold standard treatment method is the surgical excision of the tumor. This case report is a case of angiofibroma, a 32-year-old asymptomatic male patient with no evidence of clinical signs and endoscopic examination, which is recognized as a localized vascular mass lesion in the right sphenoid sinus on the cranial MR imaging. We prepared this case report that may represent an angiofibroma localized only within the sphenoid sinus which is very rare in the literature.